STRUCTURAL CHANGES OF RENAL CORPUSCLE IN THE LATE STAGES OF CHRONIC OPIOID EFFECT - Вільхова, І.В. (World of Medicine and Biology, 2014)
Given the importance of medical aspects of drug abuse problems in today’s society, the study of morphological changes of organs and systems under chronic opioid influence is the important approach of morphological studies today. The somatic diseases in drug addicts have its specific characteristics. Drugs not only affect structures of nervous system, but also cause structural changes in kidneys, which was studied by numerous researchers on autopsy and biopsy materials, in different drug users groups. However, in the literature there are no data found of renal morphofunctional changes as a result of certain dose and duration drug opioid use. The study was designed to obtain experimental data, mentioned above.The aim of conducted study was to identify the morphological changes of renal corpuscle at different stages during 14-week low doses opioid influence. The research subjects consisted of 56 mature male albino (Wistar) rats, weighting 160 to 170 gm and 4.5 to 5.5 months of age. The chronic opioid effect model was created. Intramuscular injections of nalbuphine were made once daily between 10am and 11am for a period of 98 days with a 0.212 mg/kg of primary dose and its gradual increase within acceptable therapeutic range. Histological preparations were made by a universal method. All animals were kept in vivarium conditions and the work was done according to “Guide for the Use of Laboratory Animals”. Structural changes in renal corpuscle were identified during 14-week experimental research at different terms of nalbuphine injection period. Pathomorphological changes of renal corpuscle occur during the first 6 weeks of nalbuphine injection. Strong vascular response of glomeruli was revealed after 2 weeks of the study, after 4 weeks – signs of intracapillary glomerulitis, after 6 weeks – signs of segmental glomerulosclerosis. During the next study terms (8th, 10th, 12th, 14th weeks) the same pathomorphological changes were observed, as during the first 6 weeks of the experiment. However, the number of affected renal corpuscles in each following term increases. The most intense alterations are observed in renal corpuscles of subcapsular zone. After the 6th week of the experiment, connective tissue overgrowth caused proliferation of Bowman’s capsule outer leaf. After the 8th week of the experiment, low-cubic-formed swollen epitheliocytes of outer Bowman’s capsule leaf were revealed. After 10 weeks of the study vacuolization of podocytes and enlightening of their cytoplasm were discovered in some renal corpuscles, after 12 weeks – magnification of cellular elements in macula densa area. During the entire term of experiment, protein mass with desquamated podocytes and erythrocytes was observed in Bowman’s space of some renal corpuscles. The results of the study of morphofunctional changes in kidneys affected by the chronic opioid exposure can be used in medical practice to diagnose and treat opioid nephropathy in patients with opioid addiction.